2020
DOI: 10.1016/j.scitotenv.2020.140214
|View full text |Cite
|
Sign up to set email alerts
|

Long-range air pollution transport in East Asia during the first week of the COVID-19 lockdown in China

Abstract: lockdown in China reduced long-range transport of air pollution to Taiwan.• OMI NO2 over central-north China reduced by 24% compared to previous years. • PM2.5 concentration in northernTaiwan 2 times lower compared to similar episode • CMAQ simulation with 50% reduced emission in China matches measured PM2.5 in Taiwan. • Avoided PM2.5 pollution equivalent to 0.5 μg m −3 reduction for entire winter season

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 50 publications
(69 reference statements)
1
40
1
Order By: Relevance
“…
Fig. 6 Comparison of pollutant concentration changes associated to lockdowns in Almaty ( Kerimray et al, 2020 ), Beijing, Delhi, Dubai, Mumbai, Shanghai, Rome, Zaragoza ( Chauhan and Singh, 2020 ), Malaysian cities ( Kanniah et al, 2020 ), Northern China ( Shi and Brasseur, 2020 ), Seoul, several cities in China, Tehran, Brussels, Madrid, Milan (a), Paris, New York (a) ( Bauwens et al, 2020 ), several cities in China ( Zambrano-Monserrate et al, 2020 ), Taiwan ( Griffith et al, 2020 ), the Yangtze River Delta ( Li et al, 2020 ), Barcelona ( Tobías et al, 2020 ), Milan (b) ( Collivignarelli et al, 2020 ), Western Europe ( Menut et al, 2020 ), California ( Bashir et al, 2020 ), New York (b) ( Zangari et al, 2020 ), Rio de Janeiro (a: Dantas et al, 2020 ; b: Siciliano et al, 2020 ), and Sao Paulo (a: Krecl et al, 2020 , b: Nakada and Urban, 2020 ).
…”
Section: Discussionmentioning
confidence: 99%
“…
Fig. 6 Comparison of pollutant concentration changes associated to lockdowns in Almaty ( Kerimray et al, 2020 ), Beijing, Delhi, Dubai, Mumbai, Shanghai, Rome, Zaragoza ( Chauhan and Singh, 2020 ), Malaysian cities ( Kanniah et al, 2020 ), Northern China ( Shi and Brasseur, 2020 ), Seoul, several cities in China, Tehran, Brussels, Madrid, Milan (a), Paris, New York (a) ( Bauwens et al, 2020 ), several cities in China ( Zambrano-Monserrate et al, 2020 ), Taiwan ( Griffith et al, 2020 ), the Yangtze River Delta ( Li et al, 2020 ), Barcelona ( Tobías et al, 2020 ), Milan (b) ( Collivignarelli et al, 2020 ), Western Europe ( Menut et al, 2020 ), California ( Bashir et al, 2020 ), New York (b) ( Zangari et al, 2020 ), Rio de Janeiro (a: Dantas et al, 2020 ; b: Siciliano et al, 2020 ), and Sao Paulo (a: Krecl et al, 2020 , b: Nakada and Urban, 2020 ).
…”
Section: Discussionmentioning
confidence: 99%
“…Obviously, the various forms of lockdown had an essential impact on the whole transport sector worldwide (see, for instance, reference [5] for the impact on logistics and reference [6] for the impact on air transport) and consequently on the environment and energy savings where side benefits were observed [7][8][9], as well as on economic and social activities [10,11]. The impact of COVID-19 was also intense in the field of urban mobility.…”
Section: Introductionmentioning
confidence: 99%
“…Because of this, it is difficult to determine the direct influence of the anthropogenic effects of COVID-19 on PM 2.5 concentrations observed in February and March 2020, and air pollutant concentration reduction trends during the COVID-19 period have only been confirmed by data such as surface observations and satellite images in most studies 7,20,21 . Alternatively, air quality modeling has been performed after assuming reduced emissions and the influences on the air pollutant concentration estimated 5,22,23 . Until now, there has been no study to quantitatively present the reduction of observed air pollutant concentrations influenced by COVID-19, separated from the influences of meteorological conditions and emission reduction policies.…”
mentioning
confidence: 99%